Accurate dust temperature determination in a z = 7.13 galaxy. Issue 1 (9th September 2021) - Bakx, Tom J L C; Sommovigo, Laura; Carniani, Stefano; Ferrara, Andrea; Akins, Hollis B; Fujimoto, Seiji; Hagimoto, Masato; Knudsen, Kirsten K; Pallottini, Andrea; Tamura, Yoichi; Watson, Darach
ABSTRACT: We report ALMA Band 9 continuum observations of the normal, dusty star-forming galaxy A1689-zD1 at z = 7.13, resulting in a ∼4.6 σ detection at 702 GHz. For the first time, these observations probe the far-infrared spectrum shortward of the emission peak of a galaxy in the Epoch of Reionization (EoR). Together with ancillary data from earlier works, we derive the dust temperature, Td, and mass, M d, of A1689-zD1 using both traditional modified blackbody spectral energy density fitting, and a new method that relies only on the [C ii ] 158 μm line and underlying continuum data. The two methods give $T_{\rm d} = (42^{+13}_{-7}, 40^{+13}_{-7}$ ) K, and $M_{\rm d} = (1.7^{+1.3}_{-0.7}, 2.0^{+1.8}_{-1.0})\, × {}\, 10^{7} \, M_{\odot }$ . Band 9 observations improve the accuracy of the dust temperature (mass) estimate by ∼50 per cent (6 times). The derived temperatures confirm the reported increasing T d -redshift trend between z = 0 and 8; the dust mass is consistent with a supernova origin. Although A1689-zD1 is a normal UV-selected galaxy, our results, implying that ∼85 per cent of its star-formation rate is obscured, underline the non-negligible effects of dust in EoR galaxies.